2017
DOI: 10.1098/rsfs.2016.0093
|View full text |Cite
|
Sign up to set email alerts
|

Rules to fly by: pigeons navigating horizontal obstacles limit steering by selecting gaps most aligned to their flight direction

Abstract: Flying animals must successfully contend with obstacles in their natural environments. Inspired by the robust manoeuvring abilities of flying animals, unmanned aerial systems are being developed and tested to improve flight control through cluttered environments. We previously examined steering strategies that pigeons adopt to fly through an array of vertical obstacles (VOs). Modelling VO flight guidance revealed that pigeons steer towards larger visual gaps when making fast steering decisions. In the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…These translational head movement patterns during low-speed turns are similar to the head bobbing observed in pigeons prior to landing and reminiscent of the head bobbing observed during walking in many bird species, both of which are thought to provide visual cues for landing and object localization (Davies and Green, 1988 ; Green, 1998 ). Recently, we found similar head speed fluctuations associated with vertical and horizontal obstacle negotiation flight in pigeons (Ros et al, 2017 ) Consequently, peaks in translational head speed during turning flight (Figure 3 ) may also serve to improve parallax-based perception of speed and depth by increasing translational optic flow (Dunlap and Mowrer, 1930 ; Nakayama, 1985 ; Koenderink, 1986 ; Davies and Green, 1988 ; Zeil et al, 2008 ; Eckmeier et al, 2013 ). In addition, troughs in head speed (Figure 3 ) may function to reduce motion blur, facilitate detection of independently moving objects and, possibly, dishabituate ganglion cells involved in motion sensing (Frost and DiFranco, 1976 ; Nakayama, 1985 ; Necker, 2007 ; Frost, 2009 ).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…These translational head movement patterns during low-speed turns are similar to the head bobbing observed in pigeons prior to landing and reminiscent of the head bobbing observed during walking in many bird species, both of which are thought to provide visual cues for landing and object localization (Davies and Green, 1988 ; Green, 1998 ). Recently, we found similar head speed fluctuations associated with vertical and horizontal obstacle negotiation flight in pigeons (Ros et al, 2017 ) Consequently, peaks in translational head speed during turning flight (Figure 3 ) may also serve to improve parallax-based perception of speed and depth by increasing translational optic flow (Dunlap and Mowrer, 1930 ; Nakayama, 1985 ; Koenderink, 1986 ; Davies and Green, 1988 ; Zeil et al, 2008 ; Eckmeier et al, 2013 ). In addition, troughs in head speed (Figure 3 ) may function to reduce motion blur, facilitate detection of independently moving objects and, possibly, dishabituate ganglion cells involved in motion sensing (Frost and DiFranco, 1976 ; Nakayama, 1985 ; Necker, 2007 ; Frost, 2009 ).…”
Section: Discussionsupporting
confidence: 60%
“…Importantly, the pigeon's head stabilization strategy isolates its head from body motions (Figures 3C , 4A,B ; see Videler et al, 1983 ; Bilo et al, 1985 ; Warrick et al, 2002 ; Eckmeier et al, 2008 ; Kress et al, 2015 ; Ros et al, 2017 ). As a result, both translational and angular head and body movements are uncorrelated, demonstrating reduced mechanical coupling effects between the head and body (Figures 3C , 4A,B ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenge of finding a suitable route through a cluttered environment is faced not just by honeybees, but by a number of animal species, including birds, that inhabit dense vegetation [ 14 , 20 ]. Toads, for example, are able to gauge the width of a gap between two obstacles from afar, and decide whether to go through the gap or circumvent it, depending upon its width [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by this finding, they suggest that knowing which kind of wing damage may affect aerial robot performance most could inspire more robust robot designs. Finally, Ros et al [13] contrast the challenge of flying through vertically oriented versus horizontally oriented clutter, by studying how pigeons fly through artificial forests. They found that, in comparison with flight past vertical obstacles, pigeons manoeuvred past horizontal obstacles faster and with less effort by selecting gaps most in line with their flight direction.…”
Section: Animal Flight Advancesmentioning
confidence: 99%